2008
DOI: 10.1590/s0104-14282008000400015
|View full text |Cite
|
Sign up to set email alerts
|

Cisão de cadeia na degradação termo-mecânica do poliestireno sob múltiplas extrusões

Abstract: Resumo: Determinou-se o número de cisões de cadeia gerado pela degradação termo-mecânica do poliestireno quando submetido a múltiplas extrusões. A degradação foi acompanhada pelas mudanças nas curvas de distribuição de massa molar. Seguindo-se o significado físico das massas molares médias de uma curva de MWD mostrou-se que a massa molar numérica media M n é a única que pode ser relacionada diretamente com o número de moléculas do sistema. A partir desta calculou-se o número de cadeias clivadas (ns) como uma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…At the same time, the value of polydispersity has increased. These results indicated that the process involved in the thermodegradation of PBAT is governed by the scission chain reactions [11,12] . This hypothesis is confirmed by the rheometric data since the values of torque at 10 min has decreased significantly at 200 °C.…”
Section: Methodsmentioning
confidence: 87%
“…At the same time, the value of polydispersity has increased. These results indicated that the process involved in the thermodegradation of PBAT is governed by the scission chain reactions [11,12] . This hypothesis is confirmed by the rheometric data since the values of torque at 10 min has decreased significantly at 200 °C.…”
Section: Methodsmentioning
confidence: 87%
“…This group has its concentration increased with temperature as a result of and increase in kinetic formation of it: the heat provided increases the oxygen reaction rate with macroradicals [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . On the other hand, number of extrusions yields more alkyl radicals to react with oxygen.…”
Section: Parameters Influence On Transvinylene Concentrationmentioning
confidence: 99%
“…The origin of the chain scission mechanism in polymers is due to the oxygen reaction with polymer's macromolecules, yielding alcoxi and peroxi radicals [8,9] . These radicals abstract a hydrogen atom, giving rise to the β scission, leading to a decrease in molecular weight [15] and formation of carbonyled end groups. The chain branching mechanisms is formed when alkyl macroradicals are added to vinyl groups, yielding at final stages crosslinked molecules [4,5] (Equation 1).…”
Section: Introductionmentioning
confidence: 99%
“…temperature [25] . Beyond that, the process can be dependent of initial molar mass [24,26] or not [27] . Besides the competition between these degradation processes, radical mobility becomes more important in thermomechanical degradation because the polymers are in the molten state, therefore with higher degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%